AESTHETIC EDUCATION OF PRIMARY SCHOOL STUDENTS IN THE PROCESS OF MUSIC LEARNING (Pedagogy of Higher and Secondary Education, 2003)
The main aim o f this article is to show haw musical education helps all round and harmonic education o f students.